THE EFFECT OF STORYTELLING IN IMPROVING THE STUDENTS’ SPEAKING SKILLS AT SMA NEGERI 1 RENGAT - Panji Irawan; Afrianto Afrianto; Indah Tri Purwanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The research was conducted at SMA Negeri 1 Rengat with a purpose of examining the effect of storytelling technique in enhancing the students speaking skills. The method used in executing the research was pre-experimental design, specifically one-group pre-test post-test design. The tenth grade students that include 32 students were taken as the sample by using cluster random sampling technique. The procedures in conducting the research were started by delivering the pre-test, followed by applying the treatment, and then deploying the post-test as the last step. The treatment was conducted by teaching with storytelling method through an online platform (Zoom). The result of the data analysis showed that the mean score of the pre-test is 67.5 and the average score of the post-test is 85.5. Moreover, the value of the t-test is higher than the t-table (8.44 > 1.670), which means the alternative hypothesis (Ha) is accepted, whereas the null hypothesis (Ho) is rejected. The difference between the mean score of the pre-test and the post-test as well as the hypothesis testing result clearly point out that there is a significant effect of storytelling in improving the students speaking skills.Key Words: Speaking, Speaking Skills, Storytelling.